Pengaruh Pengawasan dan Penindakan terhadap Kepatuhan Pengguna Parkir di Badan Jalan Kota Makassar - Murbayani, Murbayani; Kristomus, Benyamin (Patria Artha Management Journal, 2023)
The purpose of this study was to test and determine the effect of supervision and enforcement on parking compliance on the Makassar City road. The type of research used in this research is quantitative research with an associative approach. The data analysis technique used is multiple linear regression analysis. The results of this study partially and simultaneously prove that supervision and enforcement have a positive and significant effect on parking compliance on Makassar City roads. This means that to increase the compliance of parking users on the road, monitoring and enforcement also need to be improved.